Changes in Voice- and Swallowing-Related Symptoms After Thyroidectomy: One-Year Follow-Up Study. (March 2018) - Park, Young Min; Oh, Kyung Ho; Cho, Jae-Gu; Baek, Seung-Kuk; Kwon, Soon-Young; Jung, Kwang-Yoon; Woo, Jeong-Soo
Objective: We analyzed the changes in voice- and swallowing-related symptoms that occurred over time in patients who underwent thyroidectomy and identified any associated risk factors. Methods: One hundred and three patients who underwent thyroidectomy were enrolled. Results: The mean thyroidectomy voice-related questionnaire (TVQ) score before surgery was 12.41 ± 12.19; it significantly increased to 28.24 ± 18.01 ( P < .001) 1 month postoperatively, decreased to 24.02 ± 17.30 ( P = .014) and 20.66 ± 15.29 ( P = .023) 3 and 6 months postoperatively, respectively. It was continuously decreased to 18.83 ± 14.63 twelve months postoperatively. The temporal changes in TVQ scores between patients who underwent total thyroidectomy or lobectomy were significantly different. There was a statistically significant difference in the temporal changes in TVQ according to whether neck dissection was performed. The temporal changes in TVQ in patients with and without extrathyroidal extension were significantly different. Conclusions: Voice- and swallowing-related discomfort in patients who received thyroidectomy showed dynamic changes over time. There was a significant difference in the degree of change according to clinicopathological factors. Patients with these risk factors may benefit from appropriate patient education and various rehabilitation programs for symptom relief.